If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-7(x-8)=4x-10
We move all terms to the left:
-7(x-8)-(4x-10)=0
We multiply parentheses
-7x-(4x-10)+56=0
We get rid of parentheses
-7x-4x+10+56=0
We add all the numbers together, and all the variables
-11x+66=0
We move all terms containing x to the left, all other terms to the right
-11x=-66
x=-66/-11
x=+6
| 14+9v=41 | | 2×-2=6y-4 | | 5b+10+10b=55 | | -2(u-53)=-4 | | 6a+11+4a=71 | | 2(s-3)=94 | | 4c+8+3c=36 | | 1.5w+1.33=2 | | 3b+12+9b=24 | | 38=g/6+29 | | 2/3w+1/4=1/2 | | 3(+6)=5(x-4) | | 5v+22=92 | | 64=6u-26 | | x^2x=50 | | -7+8x=9 | | -3w+13=5(w+9) | | 6y+17=56 | | 3y+7y=28+32 | | 2x-16=4-3x | | -1(7x-9)=2x | | |5x-1|=|7-3x| | | 7(y-4)=3y-32 | | 6y-14=-2(y-5) | | 7w-4w=36-27 | | -52-x=-7x+50 | | -8(x-4)=-6x+28 | | 5y+7=78 | | 12–2(x+4)=2 | | 3x+2x-6=x+18 | | -8w+6(w-4)=-32 | | 8(h-9)=-16 |